Tiwika: Kolaborasi Musik Kaleran dalam Aransemen Kacapi - Maryana Darsim Sutisna; Lili Suparli; Dinda Satya Upaja Budi (PANTUN: Jurnal Ilmiah Seni Budaya, 2020)
"Tiwika" is a form of musical composition taken from a variety of Karawang typical arts. The arts meant are banjet mask, kacapian, and bajidoran. The process of working on the musical composition is using Kacapi waditra as a medium of expression packaged into a single unit work on a musical composition in the form of a kacapi arrangement, entitled Tiwika (Tina Wirahma Kaleran). The theoretical basis used is the theory of Atik Soepandi's Karawitan Function: Panca Pramaksara namely arkuh songs, anceran wiletan, amardawa songs, anggeran wiletan, and adumanis songs. In addition, it also adopts Rahayu Supanggah’s Garap theory. The basic concept of this work is a manifestation of traditional art which have existed into different forms with after the creativity. Tiwika's work aims to create and raises a new genre of Waditra Kacapi, especially in Karawang Regency. A waditra Kacapi in this composition can be said to be multifunctional because it can function as carrier of rhythmic, melodic, tempo, and dynamics. Although this work is based on the existing Kacapi instruments, the results show musical characteristics which are different from those in the previous arts.Keywords: Kacapi, Collaboration, Arts in Karawang